DETERMINASI TINGKAT PERTUMBUHAN EKONOMI DAN KEMISKINAN DI WILAYAH INDONESIA BAGIAN BARAT - Muhammad Yudhi Lutfi; Agustina Suparyati (Media Ekonomi, 2015)
The purpose of this study is to examine the effect of Human Development Index (HDI), Income and consumption expenditure on Poverty level in Western Indonesia region consisting of 18 provinces consisting of Central Java, West Java, East Java, Special Region of Yogyakarta, DKI Jakarta, Banten, Bangka Belitung, Bengkulu Aceh Darusalam, West Kalimantan, Central Kalimantan, North Sumatera, West Sumatera, South Sumatera, Lampung, Riau, Riau Islands and Jambi. By using a quantitative tool, the path model is divided into four substructures of equations. HDI positively affects income and consumption expenditure. The level of opinion has a positive relationship with the level of consumption whereas the income level of the community has a negative correlation to the poverty level. Consumption expenditure has a negative ridge to the poverty level and the dominant factor affecting the poverty rate directly is the human development index which means that if all access to guarantee human quality such as education, health and employment can be realized then it will reduce the poverty level in Indonesia West.